2018
DOI: 10.1093/abm/kax029
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Techniques Used in Digital Behavior Change Interventions to Reduce Excessive Alcohol Consumption: A Meta-regression

Abstract: "Behavior substitution," "Problem solving," and "Credible source" were associated with greater alcohol reduction. Many BCTs were used infrequently in DBCIs, including BCTs with evidence of effectiveness in other domains, such as "Self-monitoring" and "Goal setting."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 96 publications
2
46
0
Order By: Relevance
“…Some of our findings are consistent with previous work, for example, we found that credibility was a central facet of the acceptability of InDEx; Garnett et al’s meta-regression [25] found that the credibility of sources was associated with a reduction in alcohol consumption. Furthermore, the persuasive system design model proposes that perceived system credibility is required for technologies to be believable and more persuasive [48,49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some of our findings are consistent with previous work, for example, we found that credibility was a central facet of the acceptability of InDEx; Garnett et al’s meta-regression [25] found that the credibility of sources was associated with a reduction in alcohol consumption. Furthermore, the persuasive system design model proposes that perceived system credibility is required for technologies to be believable and more persuasive [48,49].…”
Section: Discussionsupporting
confidence: 92%
“…One possible way in which monitoring can be maintained is through the use of text messages encouraging adherence [20,21]. Another issue is the extent to which a theory is used to develop alcohol app interventions [22-24]; research has shown that more than half of digital alcohol interventions did not mention the use of theory [14,25] and only 38% used theory to inform intervention development [25]. Therefore, it is difficult to understand if it is effective in changing drinking behavior [14].…”
Section: Introductionmentioning
confidence: 99%
“…We are also much clearer that any definitive trial must be powered to detect small effects and designed to inform a pragmatic decision about whether to invest resources in recommending the app. The optimisation of the Drink Less intervention was based on the findings from this study as well as on user feedback and findings from a meta-analysis of the intervention components in digital alcohol interventions associated with effectiveness 32 . The findings from this study informed the removal of the ‘Identity Change’ module and retention of the remaining four modules.” The stopping rule in frequentist statistics means that additional trial data collected as part of an effectiveness trial for a DBCI would go to waste.…”
Section: Discussionmentioning
confidence: 99%
“…The two frameworks are complementary and in addition to designing interventions, they have been used as a method for identifying behavioural components in public health interventions and clinical trials 21. The tools have been used in previous systematic reviews to identify behaviour change techniques and functions in health interventions 22–28…”
Section: Methodsmentioning
confidence: 99%